Psycho-social Problems and Causes: Indexes of change - Nevison, Myrne B. (Canadian Journal of Counselling and Psychotherapy, 2011)
Social scientists see a pervasive crisis in our society yet also sense now a new willingness to face our problems of rapid change. This study first examines the rate and direction of change in social problems by developing indexes (comparable to the Consumer Price Index) for major problem areas. These measures show a period of relative stability in the 1950's and early 60's then worrisome inflation accompanied by out-of-control financial costs. The data on family issues particularly raise questions of future trends. The author then discusses a major cause of our difficulties, our seeming lack of strength to survive, and identifies crucial life stages where help is required.